TINDAK TUTUR DIREKTIF BAHASA MELAYU DIALEK SANGGAU - Hajjafiani, Dini; Sulissusiawan, Ahadi; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aim to study the form of directive command thrase and the directive request phrase of Malaya language in Sanggau dialect.In the scope of research, as the object of research.The research concern to the form of directive command phrase and directive request phrase. This research was conduct at the contextual speech of Malay public, when they held the natural cooperation to prepare the wedding ceremony in Tanjung Sekayam urban village, Kapuas sub-district, of Sanggau regency. This research use the pragmatic approach. The method of this research is descriptive method and the form of research is qualitative research by using the pragmatic approach. This research related to the form of directive act phrase in Malay language in Sanggau Dialect. In completing the research, the researcher used neted, interview, and record as the techniques instruments of collecting data. Result research show that then is 10 forms utterance directivecommand and 5 forms utterance directive ask. Directive act phrase can be use for the lesson of odd semester in University as the pragmatic lesson. The competency standart: describes the directive act phrase in Indonesia and the daily practice.Keywords: Speech act, directive